ANALYZING ILLOCUTIONARY ACTS IN THE WHERE HOPE GROWS MOVIE: A FOCUS ON CALVIN AND PRODUCE - Larasati, Agnes; Marginingsih, Marginingsih (University of Darussalam Gontor, 2024)
This study explores the use of illocutionary acts in the movie Where Hope Grows, focusing on the communication dynamics between the main characters, Calvin and Produce. Using a qualitative content analysis approach, the dialogues and interactions between Calvin and Produce were transcribed and coded based on John Searle's Speech Act Theory. The analysis reveals that representative acts account for 42.25% of the total illocutionary acts, while expressive acts account for 29.58%, reflecting the movie's emphasis on emotional expression and personal struggles. Directive acts contribute 23.94%, while commissive acts are found to be only 4.23% and declarative acts are absent. These findings suggest that Where Hope Grows highlights the use of representative and expressive acts to build a narrative based on the characters' beliefs and emotions, while directive and commissive acts are more limited. The study provides insights into how language is used to convey emotions, share thoughts, and influence others within the movie's context, and its implications for communication in various settings, such as personal relationships, education, and counseling.